Coping with the “coffee crisis” in Central America: the role of the Nicaraguan Red de Protección Social - Maluccio, John (International Food Policy Research Institute, 2005)
The international and local Nicaraguan media have widely reported on the “coffee crisis” in Latin America and there is substantial evidence that there has been a downturn and that this has been more severe in the coffee-growing regions. Using household panel data from a randomized community-based intervention carried out in both coffee- and noncoffee-growing areas, I examine the role of a conditional cash transfer program, the Red de Protección Social (RPS), during this downturn. While not designed as a traditional safety net program in the sense of reacting or adjusting to crises or shocks, RPS has performed like one, with larger estimated program effects for those who were more severely affected by the downturn. For example, it protected households against declines in per capita expenditures and, while not significantly depressing labor supply relative to before the program, muted additional labor supply for beneficiaries in coffee-growing areas, relative to their counterparts without the program. Beneficiaries who participated in the coffee industry as laborers before the program were more likely to have exited the coffee industry, whereas those who participated as producers were less likely to have exited. The findings are consistent with the existence of credit constraints inhibiting such transitions in the absence of the program. Overall, then, RPS appears to be playing an important part in the risk-coping strategies of households..